(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional outcome of Subscapularis release and Latissimus dorsi transfer to Infraspinatus in children with obstetric brachial plexus palsy. Methods: This retrospective Cohort study was conducted in National Orthopaedic and General Hospital Bahawalpur and Orthopaedic unit Lady Reading Hospital Peshawar.The records of all children of obstetric brachial plexus palsy fulfilling the inclusion criteria and operated with Subscapularis release and Latissimus dorsi transfer to Infraspinatus in time period extending from 25th January 2016 to 25th December 2020 were reviewed.Functional outcome was assessed by comparing pre-operative and post operative shoulder abduction and external rotation and P value was calculated with Chi-square test( P value <0.05 was considered significant). Results: We operated 19 children of obstetric brachial plexus palsy with Subscapularis release and Latissimus dorsi transfer to Infraspinatus.Male children were 13(68.42%) and female 6(31.5%).The mean follow-up was 9.78±2.48 months. Right side was involved in 11(57.89%) patients and left in 8(42.1%).Preoperatively mean external rotation was -12.63?±7.5 and abduction 65?±14.24 All patients showed significant improvement in shoulder range of motion with postoperative mean external rotation 50.78?±9.46 and abduction 117.63?±13.37( P value <0.05). Conclusion: Subscapularis release and Latissimus dorsi transfer to Infraspinatus is a good surgical technique with excellent functional outcome. We recommend this technique in children with obstetric brachial plexus palsy without spontaneous recovery.